Bioinspired polymer microstructures for directional transport of oily liquids. Issue 3 (15th March 2017) - Plamadeala, C.; Hischen, F.; Friesenecker, R.; Wollhofen, R.; Jacak, J.; Buchberger, G.; Heiss, E.; Klar, T.A.; Baumgartner, W.; Heitz, J.
Abstract : Nature has always served as an inspiration for scientists, helping them to solve a large diversity of technical problems. In our case, we are interested in the directional transport of oily liquids and as a model for this application we used the flat bug Dysodius lunatus . In this report, we present arrays of drops looking like polymer microstructures produced by the two-photon polymerization technique that mimic the micro-ornamentation from the bug's cuticle. A good directionality of oil transport was achieved, directly controlled by the direction of the pointed microstructures at the surface. If the tips of the drop-like microstructures are pointing towards the left side, the liquid front moves to the right and vice versa. Similar effects could be expected for the transport of oily lubricants. These results could, therefore, be interesting for applications in friction and wear reduction.